Near – Rings with Generalized Right n-Derivations - Adhab, Enaam Farhan (Iraqi Journal of Science, 2021)
We define a new concept, called " generalized right -derivation", in near-ring and obtain new essential results in this field. Moreover we improve this paper with examples that show that the assumptions used are necessary.